The Potential of Gold Nanorods for Larvicidal and Pupicidal Activity Against the Dengue Vector Aedes Aegypti - Razali, Nur Liyana; Morsin, Marlia; Sanudin, Rahmat; Md Shah, Nur Zehan An’nisa; Suratun Nafisah (International Journal of Integrated Engineering, 2025)
Dengue is an endemic disease in tropical areas, and it is an arthropod-borne viral infection mainly transmitted through an Aedes mosquito bite. Due to a rise in dengue transmission in urban and semi-urban regions worldwide, the disease has recently become a significant public health concern, and efficient vector control methods are required. In this study, we proposed the seed-mediated growth method of gold nanorods (GNRs) as a novel and effective tool against the I–IV larval instar and pupae of the dengue vector Aedes aegypti. GNRs have an average length of 72.80 ± 0.53 nm and a width of 16.17 ± 0.19 nm. The surface density of GNRs at 20 hours of growth aging period is 76.17± 1.98 % with a 3.94 ± 0.33 aspect ratio. The treatment was conducted on 25 larvae/cup in 100 ml of dechlorinated tap water. The larvae start to die after 48 hours.  The mortality rates of larvae after 48, 72, 96, and 120 hours, exposed to GNRs are 10.7±0.6, 24.0±1.0, 34.7±0.6 and 48.0±1.0 % respectively. Meanwhile, for pupae, the observation shows no dead pupae after 120 hours but for a longer period, several pupae die.  The survived pupae are transformed into adult mosquitoes. In conclusion, gold nanoparticles with rod shape (GNRs) have great potential as larvae and pupae treatments for the dengue vector Aedes aegypti.